ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MEMILIH KULIAH DI UNIVERSITAS TEKNOLOGI MATARAM (UTM) - MUHAMAD AHYAT; OKKY AFRIWAN; AGUS HERMANTO (Universitas Mahasaraswati K. Mataram, 2022)
This study aims to analyze the factors that influence student decisions in choosing lectures at the Mataram University of Technology (UTM). This research was conducted during September to March, namely on first semester students of the odd semester class of 2021/2022 at the Mataram University of Technology. This study is a causal associative research which means that the dependent variable is influenced by the independent variable, data collection is carried out using an instrument/questionnaire for 36 new students using the sampling method using Non-Probability Sampling. Analysis of the data used is multiple linear regression analysis and hypothesis testing using the Statistical Product and Solution (SPSS) for Windows program.The results also show that 1) Study Program variables, Accreditation Status, Tuition Fees, Promotion, Lecturer Quality, Campus Facilities, Campus Locations, Lecturer Quantity, Physical Evidence, Alumni, Image, Family and Reference Groups have a significant influence as factors that influence consumers choose to study at UTM, 2) Study Program Variable Factors have the most dominant influence on students choosing to study at UTM.